The financial crisis: Collateral damage and responses - Hanns Günther Hilpert; Stormy Mildner (Stiftung Wissenschaft und Politik (SWP), 2009)
Within just a short span of time, what started out as a local housing crisis in the US has grown into the worst global economic crisis since the Great Depression of the 1930s. However, the global slowdown in economic growth as well as the destruction of capital and prosperity worldwide have broader implications beyond their impact on the financial sector and the real economy. Dangerous distortions have emerged in many areas, including international trade, the international food, commodities, and energy markets. The pressure to justify international climate protection policies has grown. And not least of all, new risks have emerged for the cohesion of both the Eurozone and the European Union.To tackle these challenges this study is pleading for the expansion of international cooperation. Precisely because the most important lesson to be learned from the financial and economic crisis should be that global economic interdependence is a fact of life - not just between countries but also between different policy fields. Global markets need globally valid rules; global challenges can only be mastered successfully in international accord
Keywords: 320; Weltwirtschaft